2011
DOI: 10.1016/j.bbamem.2010.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Hetero-oligomeric cell wall channels (porins) of Nocardia farcinica

Abstract: The cell wall of Nocardia farcinica contains a cation-selective cell wall channel, which may be responsible for the limited permeability of the cell wall of N. farcinica for negatively charged antibiotics. Based on partial sequencing of the protein responsible for channel formation derived from N. farcinica ATTC 3318 we were able to identify the corresponding genes (nfa15890 and nfa15900) within the known genome of N. farcinica IFM 10152. The corresponding genes of N. farcinica ATTC 3318 were separately expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(37 citation statements)
references
References 33 publications
3
34
0
Order By: Relevance
“…They show in addition that the PorAPorH channel shares the characteristic fingerprints of channels such as bacterial porin (34) and also mitochondrial porin (35): closure at positive and negative potential with fast and slow kinetics, asymmetric voltage dependence, and multiple conductance states. Similar porin channels can be found in related families of bacteria, C. diphtheria, C. efficiens, and N. farcinia (8,36,37).…”
Section: Purification Of C Glutamicum and Cf-expressed Proteins-supporting
confidence: 55%
“…They show in addition that the PorAPorH channel shares the characteristic fingerprints of channels such as bacterial porin (34) and also mitochondrial porin (35): closure at positive and negative potential with fast and slow kinetics, asymmetric voltage dependence, and multiple conductance states. Similar porin channels can be found in related families of bacteria, C. diphtheria, C. efficiens, and N. farcinia (8,36,37).…”
Section: Purification Of C Glutamicum and Cf-expressed Proteins-supporting
confidence: 55%
“…In this study, we identified a channel from the cell wall of D. maris DSM 43672. A protein responsible for channel formation was identified with a molecular mass of about 120 kDa, which may be formed from a homooligomer of smaller polypeptides similar to the situation in other members of mycolata, where the cell wall channels are frequently formed by oligomers [18][19][20][21]. According to results of the lipid bilayer conductance measurements, the cell wall channel of D. maris DSM 43672 is wide, water filled and has a high preference for the passage of cations.…”
Section: Introductionmentioning
confidence: 89%
“…However, some exhibit cation selectivity (as in D. maris) whereas others are anion-selective, although it is likely that each organism will possess channels with both types of selectivity in order to facilitate uptake of the full range of hydrophilic solutes. More interestingly, some porins appear to work as hetero-oligomers [18,46] whereas others form likely homo-oligomers [47].…”
Section: Comparison Of the Cell Wall Channel Properties Of D Maris Amentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these channel-forming proteins are related to the two major families MspA and PorA (Faller et al, 2004). The MspA family is present in the genera Mycobacterium (Hillmann et al, 2007), Rhodococcus (Somalinga and Mohn, 2013), Nocardia (Kläckta et al, 2011) and Tsukamurella (Dörner et al, 2004). PorA-like proteins have exclusively been found in the genus Corynebacterium (Costa-Riu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%